AGAMA DAN KEKERASAN TERHADAP PEREMPUAN (ANALISIS GENDER DAN FILSAFAT TAOISME-ISLAM) - Fatrawati Kumari (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
Violence against women often occurs in various fields of life. The violence is a product of a patriarchal culture that is not just touching the social sphere, but also venturing into religious territory. Religion is considered as a justification and the things that make the practice of violence against women becomes a habit. View of gender bias in the various dimensions of life, including religion also took part in the practice of letting the violence against women, even seen as root causes of the violence. Through the analysis of gender and Taoism-Islam, the issue of violence against women is trying to find a comprehensive explanation for the violence seen not only physicallyquantitative, but also spiritually-qualitative. Relation equal reciprocity in the relationship becomes important bid proposed Islamic gender analysis and Taoism.